2022
DOI: 10.1101/2022.01.04.475015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infection of Microglia Elicits Pro-inflammatory Activation and Apoptotic Cell Death

Abstract: Accumulating evidence suggests that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes various neurological symptoms in coronavirus disease 2019 (COVID-19) patients. The most dominant immune cells in the brain are microglia. Yet, the relationship between neurological manifestations, neuroinflammation, and host immune response of microglia to SARS-CoV-2 has not been well characterized. Here, we report that SARS-CoV-2 can directly infect human microglia, eliciting M1-like pro-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Therefore, further studies that closely examine SARS-CoV-2 localization in astrocytic processes and/or brain microvasculature may help shed further light on SARS-CoV-2 neuroinvasiveness. We also observed rare infection of IBA + microglia; microglial infection was also recently reported by Jeong et al in a study that is available as a pre-print [41].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, further studies that closely examine SARS-CoV-2 localization in astrocytic processes and/or brain microvasculature may help shed further light on SARS-CoV-2 neuroinvasiveness. We also observed rare infection of IBA + microglia; microglial infection was also recently reported by Jeong et al in a study that is available as a pre-print [41].…”
Section: Discussionsupporting
confidence: 89%
“…Activated microglia become ameboid-shaped and express ACE2 and transmembrane protease serine subtype 2 (TMPRSS2) ( Singh, Bansal & Feschotte, 2020 ). A recent study has shown that microglia are directly infected by the SARS-COV-2 virus and can cause self-apoptosis, thereby causing a reduction in the number of microglia which leads to further infiltration of the virus ( Jeong et al, 2022 ). Secondly, infection with SARS-COV-2 significantly increased the level of TNF-α and IL-6, suggesting that activated microglia lead to neuroinflammation ( Jeong et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that microglia are directly infected by the SARS-COV-2 virus and can cause self-apoptosis, thereby causing a reduction in the number of microglia which leads to further infiltration of the virus ( Jeong et al, 2022 ). Secondly, infection with SARS-COV-2 significantly increased the level of TNF-α and IL-6, suggesting that activated microglia lead to neuroinflammation ( Jeong et al, 2022 ). A Post-mortem study of brains of patients deceased from COVID-19 showed neuropathological signs of microglial activation ( Matschke et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study has limitations that must be considered. Firstly, we focused exclusively on the airway epithelium, and it is now established that SARS-CoV-2 is capable of infecting other cell lineages including monocytes, monocyte-derived macrophages, and microglia (Boumaza et al, 2021;Jeong et al;Liu et al, 2021). It is possible that Gal-9 does not exert similar effects on viral replication or immune signaling in other target cell types.…”
Section: Discussionmentioning
confidence: 99%